Risk-benefit balance assessment of SSRI antidepressant use during pregnancy and lactation based on best available evidence – an update. Issue 10 (3rd October 2019) - Fischer Fumeaux, Céline J; Morisod Harari, Mathilde; Weisskopf, Etienne; Eap, Chin B; Epiney, Manuella; Vial, Yvan; Csajka, Chantal; Bickle Graz, Myriam; Panchaud, Alice
ABSTRACT: Introduction : Depression affects 300 million individuals worldwide. While selective serotonin reuptake inhibitors (SSRI) are one of the first-line pharmacological treatments of major depression in the general population, there is still uncertainty regarding their potential benefits and risks during pregnancy. Areas covered : Outcomes requisite for a proper risk/benefit assessment of SSRI in pregnancy and lactation were considered: (a) potential risks associated with untreated depression, (b) effectiveness of different treatment options of depression, (c) potential risks associated with SSRI. Expert opinion : Despite the growing amount of literature on SSRI use during pregnancy, no new trials assessing the benefits of SSRIs on maternal depression were found. In the light of new data regarding the potential risks, depressed SSRI-treated pregnant women and their children seem at increased risk for several complications (mostly of small absolute risk). The interpretation of these findings remains quite similar to our previous review as the available methodology does not allow to disentangle the potential effect of SSRIs from those of the disease itself or/and of its unmeasured associated risk factors. Thus, in pregnant or lactating women who require a pharmacological treatment, SSRIs can still be considered as appropriate when effective as the abundant data support their relative safety.